2006
DOI: 10.1055/s-2006-951601
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Imaging in the 21st Century

Abstract: Imaging of the liver has progressed rapidly during the past decade with continued advancement of current ultrasound, computed tomography, and magnetic resonance imaging (MRI). Each modality not only has seen refinement enabling better anatomic characterization of disease but also has received strength from the addition of new techniques to its resources. New contrast agents have become available for all modalities and some agents, particularly for MRI, have opened the way for better functional assessment. MRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 57 publications
0
7
0
2
Order By: Relevance
“…Although the good spatial resolution of US ensures high sensitivity in detecting focal liver lesions, the technique has less capability for characterising small lesions, particularly in the cirrhotic liver [10,12]. In the past 10 years, hepatic US imaging has experienced a technological revolution [13] brought about by the introduction of microbubble contrast agents that have made it possible to overcome the limitations of baseline ultrasound in identifying and characterising lesions [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the good spatial resolution of US ensures high sensitivity in detecting focal liver lesions, the technique has less capability for characterising small lesions, particularly in the cirrhotic liver [10,12]. In the past 10 years, hepatic US imaging has experienced a technological revolution [13] brought about by the introduction of microbubble contrast agents that have made it possible to overcome the limitations of baseline ultrasound in identifying and characterising lesions [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…L'elevata risoluzione spaziale dell'US garantisce una buona sensibilità nella identificazione delle lesioni focali epatiche, ma presenta un minor potenziale nella caratterizzazione delle lesioni più piccole, in particolare nel fegato cirrotico [10,12]. L'imaging del fegato mediante ultrasuoni è stato rivoluzionato tecnologicamente negli ultimi dieci anni [13], merito dei mezzi di contrasto (MdC) a microbolle che offrono l'opportunità di valicare i limiti dell'ecografia basale nella identificazione e caratterizzazione delle lesioni [14][15][16][17][18][19][20].…”
Section: Introduzioneunclassified
“…In fact, only 29.2% of patients with benign or most likely benign lesions were included in this group. This small patient number was due to several factors: 1) most of the patients had been referred and had already received CT exams, which explains the small number of MRI performed as the initial examination in the casuistry; this situation contrasts with the recommendations of many authors, who judge the MRI as the exam of choice in the diagnostic evaluation of focal liver lesions 2 , 10 , 12 , 15 , 28 , 25 ; the MRI performed in the follow-up examinations in the present study were able to clarify the diagnoses in at least six patients allocated into groups 2 and 3 who had not been diagnosed through CT and who had small hemangiomas, preserved areas of parenchyma in fatty liver and FNH; 2) a significant portion of patients (28.4%) had small lesions between 1 and 2 cm in size; the central scar of FNH and the heterogeneous areas of necrosis or hemorrhage of HA are infrequent in small lesions, which hampers the differential diagnosis of such lesions; 3) the definition of HA was based on rigid criteria, only including cases in which intra- or perilesional hemorrhaging was present; this feature was chosen because bleeding, although uncommon (21 - 40% of cases) 1 , is a reliable finding in the differentiation of FNH; 4) MRI with hepatic-specific contrast was not part of the early stage of the study, having been used in only a few cases in the last two years; the use of hepatic-specific contrast in MRI has been considered as the best way to establish a differential diagnosis between HA and FNH. In a recent meta-analysis that included 10 studies and 304 patients with FNH subjected to MRI with gadoxetic acid (Gd-EOB-DTPA), Suh et al 26 concluded that High/Iso signal intensity on the hepatobiliary phase of the examination occurs in most patients (94-97%) with FNH.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to detect early and intermediate stages of fibrosis using conventional ultrasound with Doppler assessment of the hepatic vasculature is unsatisfactory [27]. CT offers improved resolution of early morphological changes with cirrhosis but has low accuracy in fibrosis detection [28]. In fact, quantitative assessment of the density distribution of liver parenchyma showed that only diffuse steatosis and active alcoholic cirrhosis had significantly different mean hepatic attenuation values [29].…”
Section: Imaging Techniquesmentioning
confidence: 99%